Diagnostic Performance of Advanced Metal Artifact Reduction MRI for Periprosthetic Shoulder Infection. (3rd August 2022) - Fritz, Jan; Meshram, Prashant; Stern, Steven E.; Fritz, Benjamin; Srikumaran, Uma; McFarland, Edward G.
Abstract : Background: The diagnosis of periprosthetic shoulder infection (PSI) in patients with a painful arthroplasty is challenging. Magnetic resonance imaging (MRI) may be helpful, but shoulder implant-induced metal artifacts degrade conventional MRI. Advanced metal artifact reduction (MARS) improves the visibility of periprosthetic bone and soft tissues. The purpose of our study was to determine the reliability, repeatability, and diagnostic performance of advanced MARS-MRI findings for diagnosing PSI. Methods: Between January 2015 and December 2019, we enrolled consecutive patients suspected of having PSI at our academic hospital. All 89 participants had at least 1-year clinical follow-up and underwent standardized clinical, radiographic, and laboratory evaluations and advanced MARS-MRI. Two fellowship-trained musculoskeletal radiologists retrospectively evaluated the advanced MARS-MRI studies for findings associated with PSI in a blinded and independent fashion. Both readers repeated their evaluations after a 2-month interval. Interreader reliability and intrareader repeatability were assessed with κ coefficients. The diagnostic performance of advanced MARS-MRI for PSI was quantified using sensitivity, specificity, and the area under the receiver operating characteristic curve (AUC). When applying the International Consensus Meeting (ICM) 2018 criteria, of the 89 participants, 22 (25%) were deemed as being infected and 67 (75%) were classified as being not infected (unlikely to have PSA and not requiring a surgical procedure during 1-year follow-up). Results: The interreader reliability and intrareader repeatability of advanced MARS-MRI findings, including lymphadenopathy, joint effusion, synovitis, extra-articular fluid collection, a sinus tract, rotator cuff muscle edema, and periprosthetic bone resorption, were good (κ = 0.61 to 0.80) to excellent (κ > 0.80). Lymphadenopathy, complex joint effusion, and edematous synovitis had sensitivities of >85%, specificities of >90%, odds ratios of >3.6, and AUC values of >0.90 for diagnosing PSI. The presence of all 3 findings together yielded a PSI probability of >99%, per logistic regression analysis. Conclusions: Our study shows the clinical utility of advanced MARS-MRI for diagnosing PSI when using the ICM 2018 criteria as the reference standard. Although the reliability and diagnostic accuracy were high, these conclusions are based on our specific advanced MARS-MRI protocol interpreted by experienced musculoskeletal radiologists. Investigations with larger sample sizes are needed to confirm these results. Level of Evidence: Diagnostic Level III . See Instructions for Authors for a complete description of levels of evidence.